To question about features of realization of judicial procedure powers by judges of the Supreme Court ofUkraine - Нижник, Ніна Романівна; Муза, Олег Валентинович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article discusses the features of judicial procedure powers by judges of the Supreme Court ofUkraine, who were seconded to work in the High Qualification Commission of Judges of Ukraine.